THE INFLUENCE OF ADVERTISING CAMPAIGNS ON CONSUMER LIKES: THEORETICAL ASPECT (Development Service Industry Management, 2024)
The aim of this article is a thorough analysis of various channels and methods of advertising communication in the context of their influence on contemporary society. Methodology. The article explores traditional (television, radio, press, outdoor advertising) and digital (social networks, personalization) mass media tools. Scientific novelty is revealed in a detailed analysis of the "Share a Coke" advertising strategy by The Coca-Cola Company. Results. The research results confirm the key role of advertising in shaping consumer preferences and determine its impact on cultural and economic aspects of modern life. Scientific. Novelty. Scientific novelty is demonstrated in a detailed analysis of the "Share a Coke" advertising strategy by The Coca-Cola Company, emphasizing the effectiveness of innovative approaches. Practical Significance. The concluding remarks of the article emphasize the importance of adapting advertising strategies to changes in consumer preferences, highlighting advertising as a strategic factor in brand-consumer interaction. Practical significance lies in the opportunity to use the acquired knowledge to improve the effectiveness of advertising campaigns and strengthen brand loyalty
Keywords: advertising communication; consumer preferences; mass media; digital advertising; advertising strategies; cultural influence; advertising effectiveness; brand loyalty; innovative approaches